Spatio-temporal modeling of 210Pb transportation in lake environments - Kuelahci, Fatih; Sen, Zekai (Elsevier Science Bv, 2009)
Radioactive particle movement analysis in any environment gives valuable information about the effects of the concerned environment on the particle and the transportation phenomenon. In this study, the spatiotemporal point cumulative semivariogram (STPCSV) approach is proposed for the analysis of the spatiotemporal changes in the radioactive particle movement within a surface water body. This methodology is applied to the Pb-210 radioactive isotope measurements at 44 stations, which are determined beforehand ill order to characterize the Keban Dam water environment on the Euphrates River in the Southeastern part of Turkey. It considers the contributions coming from all the stations and provides information about the spatio-temporal behavior of (210)pb in the water environment. After having identified the radii of influences at each station it is possible to draw maps for further interpretations. In order to see holistically the spatial changes of the radioisotope after 1st, 3rd and 5th hours, the radius of influence maps are prepared and interpreted accordingly. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Cumulative semivariogram; Radionuclide; Lake; Spatial analysis; Contamination